ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PETANI DALAM PENJUALAN PADI KE TENGKULAK DI KECAMATAN JATILAWANG KABUPATEN BANYUMAS - Hermanto Hutabarat (Universitas Muhammadiyah Purwokerto, 2013)
Most of the population in Sub Jatilawang subsistence are farmers . In carrying out its activities people still rely on middlemen to facilitate their business . The purpose of this study was to determined the factors that influence farmers in selling paddy to middlemen in District Jatilawang Banyumas. The method used was a survey method . Header retrieval techniques using simple random sampling . The samples used were 98 respondents .The results of thist study are rice production , the price of rice , the family consumption ( F = 610.484 ) and cash costs may affect the sales of rice farmers to middlemen ( t1 = 28.5 , t2 = 0.057 , t3 = t4 = 12.209 and 11.209 ) . But individually variable does not affect the sale price of paddy to farmers . The variables that most influence on rice sales to middlemen ie rice production variables ( X1 = 28.534 , X2 = 0.057 , X3 = X4 = 12.209 and 11.107 ). Keyword: Seeling, paddy and middleman.